The Transition to a Coresidential Partnership: Who Moves and Who Has the Partner Move In? - Sandra Krapf; Clara H. Mulder; Michael Wagner (Population Research and Policy Review, 2021)
Moving into a joint household is an important step in the process of union formation. While a growing body of literature investigates differences between those couples who start coresidence and those who do not, we know little about the likelihood of moving upon the start of coresidence. The aim of this paper is to investigate how individual and couple-level characteristics are associated with moving, or having a partner move in, at the start of coresidence. We use data from 10 waves of the German Family Panel pairfam for those who started coresidence (n0.167em=0.167em983) and estimate logistic regression models of moving versus having a partner move in. The respondents in the sample are quite young with a mean age of 27. For long-distance relationships, those with a higher level of education than their partner and women who were living in close proximity to their parents were less likely to move. In short-distance relationships, respondents living in the parental home or in crowded housing were more likely to move than those living in uncrowded housing. In contrast with previous research, we did not find that women were more likely to move than men. Our results highlight that factors like educational resources, housing demands, and local family ties have differential effects on moving decisions at the start of coresidence depending on the distance moved.
Keywords: 300; Coresidence; Union formation; Relocation; Migration